Integrated CO2 Capture and Utilization Using Non-Thermal Plasmolysis - Moss, Matthew; Reed, Daniel G.; Allen, Ray W. K.; Styring, Peter (Frontiers in Energy Research, 2017)
In the presented work, 2 simple processes for carbon dioxide (CO2) capture and utilisation have been combined to form a whole systems approach to carbon capture and utilisation (CCU). The first stage utilises a pressure swing adsorption (PSA) system, which offers many benefits over current amine technologies. It was found that high selectivity can be achieved with rapid adsorption/desorption times whilst employing a cheap, durable sorbent that exhibits no sorbent losses and is easily regenerated by simple pressure drops. The PSA system is capable capturing and upgrading the CO2 concentration of a waste gas stream from 12.5% to a range of higher purities. As many CCU end processes have some tolerance towards impurities in the feed, in the form of nitrogen (N¬2) for example, this is highly advantageous for this PSA system since CO2 purities in excess of 80% can be achieved with only a few steps and minimal energy input. Non-thermal plasma is one such technology that can tolerate, and even benefit from, small N2 impurities in the feed, therefore a 100% pure CO2 stream is not required. The second stage of this process deploys a nanosecond pulsed corona discharge reactor to split the captured CO2 into carbon monoxide (CO), which can then be used as a chemical feedstock for other syntheses. Corona discharge has proven industrial applications for gas cleaning and the benefit of pulsed power reduces the energy consumption of the system. The wire-in-cylinder geometry concentrates the volume of gas treated into the area of high electric field. Previous work has suggested that moderate conversions can be achieved (9%), compared to other non-thermal plasma methods, but with higher energy efficiencies (>60%).